SYMBOLIC MEANING OF COSTUMES AND PROPERTY GONG DANCE OF THE DAWAN TRIBE NANSEAN VILLAGE - Kadek Paramitha Hariswari; Flora Ceunfin; Yohanis Devriezen Amasanan (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
Gong Dance is a profane dance of the Dawan Tribe community in Insana District, North Central Timor (TTU) Regency, East Nusa Tenggara Province which is usually danced in various events, both traditional events and as a reception dance.a symbol of authority, toughness, courage and masculinity of a Dawan tribe man. In particular, the symbolic meaning of Gong Dance is analyzed in terms of the costumes and properties used which are divided into three parts, namely the head which consists of pilu and pet no’o, body part consists of foke, molo, kain beti, pasu, sbeta and aluk. The leg consists of poentuf, bukhaef and giring-giring. While the properties of the gong dance are sumi and selendang. To analyze the symbolic meaning of the costumes and properties of the gong dance using qualitative descriptive analytical methods. Data obtained through observation and interviews as well as documentation.Keywords: Gong Dance; Symbolic Meaning; Costume and PropertyMAKNA SIMBOLIK PADA KOSTUM DAN PROPERTITARI GONG SUKU DAWAN DESA NANSEAN AbstrakTari  Gong merupakan sebuah tari profan masyarakat Suku Dawan yang ada di Kecamatan Insana Kabupaten Timor Tengah Utara (TTU) Provinsi Nusa Tenggara Timur yang biasanya ditarikan dalam berbagai acara baik acara adat maupun sebagai tarian penerimaan tamu. Tari Gong secara umum dimaknai oleh masyarakat Suku Dawan sebagai simbol kewibawaan, ketangguhan, keberanian dan kejantanan seorang laki-laki Suku Dawan. Secara khusus, makna simbolik Tari Gong dianalisis dari segi kostum dan properti yang digunakan yang terbagi menjadi tiga bagian yakni bagian kepala yang terdiri dari pilu dan pet no’o, bagian badan terdiri dari foke, molo, kain beti, pasu, sbeta dan aluk. Bagian kaki terdiri dari poentuf, bukhaef dan giring-giring. Sedangkan properti tari gong adalah sumi dan selendang. Untuk menganalisis makna simbolik kostum dan properti tari gong menggunakan metode kualitatif deskriptif analitikal. Data diperoleh melalui observasi dan wawancara serta dokumentasi.Kata Kunci: Tari Gong, Makna Simbolik, Kostum dan Properti